Efektivitas Manajemen Sumber Daya Manusia (Studi Kasus Penerapan Audit Manajemen pada Hotel X Seminyak) - Sembiring, Sony Ricardo; Budiartha, Ketut (E-Jurnal Akuntansi; Vol 25 No 2 (2018), 2018)
This research is a qualitative research with a case study approach. The purpose is to determine the effectiveness of human resource management in X Seminyak Hotel. The data collection used interview with purposive informants, observation and documentation method. This management audit research instrument uses the audit program as a guidelines and effectiveness assessment as analysis technique. The results of the study found that recruitment, training and development, career planning and development, and termination of employment programs at organization had run effectively. The program selection and placement, as well as occupational health and safety are classified as quite effective, while the planning program is classified as ineffective. Based on these findings several recommendations for improvement were suggested such as the establishment of planning standards, the addition of new workforce, and socialization the importance of work safety. These recommendations are given so human resources management activities can run effectively. Keyword:   audit management, human resources (HR), effectiveness, audit program